Mapping the Landscape, Influence, and Publication Visibility of Activity-Based Costing (ABC) and Activity-Based Management (ABM): A Comprehensive Bibliometric Analysis - Rizky Nuryanti; Syafrozi Haqi; Nurika Restuningdiah; Puji Handayati (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
As business complexity and global competition intensify, the limitations of traditional cost accounting systems in providing relevant information for strategic decision-making become increasingly apparent. This has driven the adoption of Activity-Based Costing (ABC) and subsequently Activity-Based Management (ABM), which have evolved as vital tools to accurately allocate costs based on activities and transform this information into value-enhancing and efficiency-improving strategies. This study aims to map the landscape, influence, and visibility of ABC and ABM publications through a comprehensive bibliometric analysis using VOSviewer. The research method involves a Systematic Literature Review (SLR) for data collection and screening from 488 publications (2023-2025) indexed in Scopus from Google Scholar, followed by data analysis and visualization of co-authorship and keyword co-occurrence networks. The analysis results show the dominance of core concepts such as "activity-based costing/management," "activity," "costing," and "management" as the foundation of research. Identified thematic clusters include the basic applications of ABC and its impact on performance, managerial aspects of ABM, efficiency, and the challenges and benefits of implementation. Temporal trends indicate a shift in the focus of recent research towards the strategic and managerial contributions of ABM/ABC in enhancing efficiency, supporting decision-making, and driving organizational performance. Density visualizations confirm research "hotspots" in these areas, while also highlighting potential research gaps for the future. The conclusion demonstrates the continuous relevance of ABC and ABM as adaptive cost and performance management tools, as well as the evolution of the discipline continually adapting to modern business's strategic needs, guiding researchers and practitioners for further exploration.